Comparative Efficacy of Interventional Therapies for Early-stage Hepatocellular Carcinoma: A PRISMA-compliant Systematic Review and Network Meta-analysis. Issue 15 (April 2016) - Lan, Tian; Chang, Lei; MN, Rahmathullah; Wu, Long; Yuan, Yu-Feng
Abstract : Abstract: There are several interventional therapies that improve the prognosis and increase the survival rate of early-stage hepatocellular carcinoma (early-stage HCC), but it is uncertain about whether one is superior to others, and available researches investigating the comparative effects of different treatments are limited. The main objective of this Bayesian network meta-analysis was to compare the efficacy of these different treatment strategies for early-stage HCC and rank these interventions for practical consideration. We performed an electronic search of PubMed, Embase, and Cochrane Library, and extracted data from randomized controlled trials that compared different interventional therapies for early-stage HCC. Direct comparison and network meta-analyses were conducted with Aggregate Data Drug Information System software. Consistency models were created to determine whether there was a significant difference between any 2 therapies, and cumulative probability was used to rank different treatments. Twenty-one randomized controlled trials involving 2691 patients were included. In our network meta-analysis, the combination therapy of transcatheter arterial chemoembolization (TACE) and radiofrequency ablation (RFA) was associated with better 1-year survival rate, as compared with hepatic resection alone ( P < 0.05, odds ratio [OR] 0.25, 95% confidence interval [CI] 0.06–0.83), percutaneous ethanol injection (PEI) alone ( P < 0.05, OR 0.13, 95% CI 0.03–0.45), and RFA alone ( P < 0.05, OR 0.23, 95% CI 0.07–0.70). TACE + RFA had a higher 3-year survival rate than PEI alone ( P < 0.05, OR 0.32, 95% CI 0.15–0.72) and RFA alone ( P < 0.05, OR 0.45, 95% CI 0.24–0.87). And there was a statistical difference between RFA + PEI and PEI alone ( P < 0.05, OR 0.33, 95% CI 0.12–0.93) for 3-year survival rate. The results of rank test and cumulative probability showed that TACE + RFA ranked highest on the evaluation of 1-year, 3-year, and 5-year survival rate. Based on Bayesian network meta-analysis combining direct and indirect comparisons, the combination therapy of TACE and RFA seemed to be the most effective strategy for early-stage HCC.